Fed-Batch Fermentation of Saccharomyces pastorianus with High Ribonucleic Acid Yield - Hao Chen; Jinjing Wang; Qi Li; Xin Xu; Chengtuo Niu; Feiyun Zheng; Chunfeng Liu (Foods, 2022)
(1) Background: The degradation products of ribonucleic acid (RNA)are widely used in the food and pharmaceutical industry for their flavoring and nutritional enhancement functions. Yeast is the main source for commercial RNA production, and an efficient strain is the key to reducing production costs; (2) Methods: A mutant Saccharomyces pastorianus G03H8 with a high RNA yield was developed via ARTP mutagenesis and fed-batch fermentation was applied to optimize production capacity. Genome sequencing analysis was used to reveal the underlying mechanism of higher RNA production genetic differences in the preferred mutant; (3) Results: Compared with the highest RNA content of the mutant strain, G03H8 increased by 40% compared with the parental strain G03 after response surface model optimization. Meanwhile, in fed-batch fermentation, G03H8′s dry cell weight (DCW) reached 60.58 g/L in 5 L fermenter by molasses flowing and RNA production reached up to 3.58 g/L. Genome sequencing showed that the ribosome biogenesis, yeast meiosis, RNA transport, and longevity regulating pathway were closely related to the metabolism of high RNA production; (4) Conclusion: S. pastorianus G03H8 was developed for RNA production and had the potential to greatly reduce the cost of RNA production and shorten the fermentation cycle. This work lays the foundation for efficient RNA content using S. pastorianus.